In the dark places an Inspector Banks novel - Robinson, Peter 1950- (New York, NY William Morrow, an imprint of HarperCollinsPublishers, 2015)
"As Banks and his team follow what few clues they have, desperate to find the missing boy, who holds the key to the puzzle, they find themselves branching out in different directions. As the end game becomes a race against time, even Banks's team isn't safe from the rage of the hunted animal"--
105553
Keywords: Banks, Alan -- (Fictitious character); Fiction -- Suspense; Mystery fiction; Detective and mystery fiction; Thrillers (Fiction)